Contribuições à identificação de regimes operacionais de centrais geradoras a biogás de aterros sanitários conectadas à rede - Brignol, Wagner da Silva (2013)
This paper aims to propose the development of strategies for setting the best times of the day when a distributed generation of electricity (GD), which uses the biogas as fuel chemical reactions in urban solid waste, deposited in landfills sanitary, can dispatch electricity as a distribution network in order to meet the quality indices of power (PQ) established in PRODIST / ANEEL (2010). For the development of this work was carried out to evaluate the electrical characteristics of a distribution network (feeder) belonging to the distribution system of the concession area of the State Company for Electric Power Distribution (CEEE-D), which serves a landfill located in the Greater Porto Alegre, which has energy potential for installation of GD. The methodology used to define the best operating systems was the methodology multicriterial Analytic Hierarchy Process - AHP, using the M-MACBETH software. In this methodology were considered quantitative and qualitative criteria. Quantitative criteria are represented by real data, which indicate directly the value of each technical feature in the process, and they suffer direct influence with the inclusion of DG in the distribution network. Qualitative criteria are those with imprecision in their values and / or difficulties in their quantification in the case of this study, Ancillary Services. The criteria used in this study were chosen and valued by agents Decision (AD) composed of Specialists electricity distributor and Specialists by GD, which together defined the needs and the weights of these criteria. The evaluation takes place in conjunction between the quantitative and qualitative criteria and the result is a classification (ranking) of times when it is most advantageous to insert the energy generated by the GD system.